2019
DOI: 10.1101/618256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An association between the gut microbiota and immune cell dynamics in humans

Abstract: 22The gut microbiota influences the development and homeostasis of the mammalian immune system 1-23 3 , can alter immune cell compositions in mice [4][5][6][7] , and is associated with responses to immunotherapy 24 that rely on the activity of peripheral immune cells [8][9][10][11][12] . Still, our understanding of how the microbiota 25 modulates circulatory immune cells remains limited, particularly in humans where a lack of 26 manipulative experiments makes inference challenging. Here we overcome this challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…We also found a high correlation between certain intestinal microbiota and master transcription factors of host immunity during P. yoelii infection. Currently, we still cannot identify their causality [37]. The intestinal microbiota can produce serval metabolic repertoire as signal molecules, such as short-chain fatty acids (SCFAs), or increase the host product, such as bile acid, to regulate the phenotype of antiin ammatory cells [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…We also found a high correlation between certain intestinal microbiota and master transcription factors of host immunity during P. yoelii infection. Currently, we still cannot identify their causality [37]. The intestinal microbiota can produce serval metabolic repertoire as signal molecules, such as short-chain fatty acids (SCFAs), or increase the host product, such as bile acid, to regulate the phenotype of antiin ammatory cells [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…We also found a high correlation between certain intestinal microbiota and master transcription factors of host immunity during P. yoelii infection. Currently, we still cannot identify their causality [37]. The intestinal microbiota can produce serval metabolic repertoire as signal molecules, such as short-chain fatty acids (SCFAs), or increase the host product, such as bile acid, to regulate the phenotype of anti-inflammatory cells [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Xavier's group is collaborating with clinicians to understand how antibiotics affect the gut microbiomes of bone-marrow-transplant recipients, whose immune systems are suppressed to minimize rejection of the transplant. They found that the resulting microbial disruptions can markedly affect the function of the immune system after the transplant, and that supplementing individuals with healthy microbial populations could improve their recovery 4 .…”
Section: Just Part Of the Picturementioning
confidence: 99%